2007
DOI: 10.1074/jbc.m704864200
|View full text |Cite
|
Sign up to set email alerts
|

The Site of Action of the Antiterminator Protein N from the Lambdoid Phage H-19B

Abstract: Transcription antitermination by N proteins of lambdoid phages involves specific interactions of the C-terminal domain of N with the elongation complex (EC). The interacting surface of N on the EC is unknown, knowledge of which is essential to understand the mechanism of antitermination. Specific cleavage patterns were generated near the active site Mg Transcription elongation complexes (EC)3 formed by the Escherichia coli RNA polymerase (RNAP) are exceptionally stable and highly processive (1). The stability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 53 publications
1
18
0
Order By: Relevance
“…The λN protein, whose interaction with RNAP is facilitated by host proteins (NusA, NusB, NusE and NusG), binds to the λ nut site in the nascent RNA (43). How λN assists RNAP to read through terminators remains unclear (44), but its site of action appears to be in proximity to the RNA:DNA hybrid of the transcription elongation complex (45). As mentioned previously, the assembly of the complete antitermination complex is required for processive antitermination and begins with the formation of the NusB–NusE–BoxA complex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The λN protein, whose interaction with RNAP is facilitated by host proteins (NusA, NusB, NusE and NusG), binds to the λ nut site in the nascent RNA (43). How λN assists RNAP to read through terminators remains unclear (44), but its site of action appears to be in proximity to the RNA:DNA hybrid of the transcription elongation complex (45). As mentioned previously, the assembly of the complete antitermination complex is required for processive antitermination and begins with the formation of the NusB–NusE–BoxA complex.…”
Section: Discussionmentioning
confidence: 99%
“…λN protein (gray) binds BoxB (8–11) and also possibly NusE (this work). λN protein binds RNAP near the transcription bubble (45). NusA (red) stabilizes these interactions by interacting with the λ nut spacer RNA between BoxA and BoxB (12), and with λN protein (51) through NusA SKK (S1-KH1-KH2) and AR1 domains, respectively, while anchoring the complex to RNAP through the NusA NTD and AR2 domains (48–50).…”
Section: Discussionmentioning
confidence: 99%
“…The proteins involved in rrn transcription antitermination in E. coli include a combination of transcription factors, NusA and NusG, known to associate with RNA polymerase (10,11,30,32,50), ribosomal proteins NusE (S10), S4 (34,37,47), and NusB, an antitermination factor required in both the lambda and rrn AT systems (13,24,35,39,43,47). In Bacillus subtilis a series of experiments performed with green fluorescent protein fusions of NusA, NusB, and NusG have directly visualized the association of these factors with RNA polymerase (16,17).…”
mentioning
confidence: 99%
“…We have earlier shown that RNAP mutations in and around the RNA exit channel perturb N action (23) and also proposed that the N C-terminal domain may penetrate into the core of the EC through this exit channel (33). Here, we propose that in addition to N-EC direct interactions, N-NusA NTD binding also affects the adjacent ␤-flap regions.…”
Section: Discussionmentioning
confidence: 81%